Artificial Intelligence, Big Data, and the Role of Universities - Naidoo, Rajani (International Higher Education, 2025)
<h3 id="artificial-intelligence-ai-and-big-data-are-transforming-economies-societies-and-institutions-raising-critical-concerns-for-democracy-intellectual-autonomy-and-global-citizenship-while-ai-offers-immense-benefits-it-is-also-leveraged-by-tech-elites-to-consolidate-power-erode-regulation-and-act-against-the-global-good-this-article-discusses-some-of-these-key-dimensions-and-outlines-some-important-research-directions-including-prioritizing-interdisciplinary-research-on-how-political-and-economic-power-can-leverage-technology-to-harness-or-prevent-ai-from-being-deployed-for-the-benefit-of-people-and-our-planet" data-pm-slice="1 1 []">Artificial intelligence (AI) and big data are transforming economies, societies, and institutions, raising critical concerns for democracy, intellectual autonomy, and global citizenship. While AI offers immense benefits, it is also leveraged by tech elites to consolidate power, erode regulation, and act against the global good. This article discusses some of these key dimensions and outlines some important research directions, including prioritizing interdisciplinary research on how political and economic power can leverage technology to harness or prevent AI from being deployed for the benefit of people and our planet.